An exploratory investigation on the microbiological quality of dim sum (pork dumplings) sold in Chiang Mai, Thailand - Warangkhana Chaisowwong (2018)
An exploratory investigation was conducted to determine the microbiologcal quality of pork dumplings (dim sum) sold in Chiang Mai, Thailand. 90 deep frozen industrial samples were collected from 3 brands and another 90 ready-to-eat samples from small enterprises (market samples, street vendors and restaurants). Although the deep frozen dim sum samples showed on average an internal temperature of only x̄±s = -5.5±1.8 °C at the point of selling, their counts of total aerobic mesophilic bacteria (x̄±s = 1.38±0.77 log cfu/g) were significantly lower than the APCs (= Aerobic Plate Count) of the small enterprises (x̄±s = 3.12±1.83 log cfu/g). The corresponding values were x̄±s = 0.71 ±0.05 resp. x̄±s = 1.25±0.70 log cfu/g for lactic acid bacteria, x̄±s = 0.8±02.2 resp. x̄±s = 24.2±43.2 MPN/g for Enterobacteriaceae and xx̄±s = 0.6±1.7 resp. xx̄±s = 24 2±43.2 MPN/g for coliforms. Pseudomonas spp. were detected in 11 % of the market samples and none of the dumplings passed the detection limit of 102 cfu/g for coagulase-positive staphylococci. The percentage of small enterprises which exceeded the official Thai microbial standards for cooked-chilled food (to be reheated before consumption) for the total amount of aerobic bacteriae and coliforms were 12 % and 11 %, respectively. Storing at room temperature for 6-8 hours raised the APCs of ready-to-eat dim sum for two power of ten and reheating of these items to 69 °C reduced the contamination to the initial level. However, two main conclusions can be drawn from the results of this exploratory investigation. To enhance the hygienic quality of dim sum sold in small enterprises in Chiang Mai the personnel training of employees as well as the governmental food inspection should be improved. Concerning the deep frozen industrial pork dumplings it is only necessary to better monitor the temperature of the freezers located in the superstores and eventually adjust when necessary. © M. & H. Schaper GmbH & Co.